Evaluasi Kerentanan Bangunan Gedung Terhadap Gempa Bumi Dengan Rapid Visual Screening (RVS) Berdasarkan Femad 154 - Rahmatul Firdaus; Alex Kurniawandy; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Earthquake is a disaster that could bring a disadvantage on society, either materials or lifes. Although Pekanbaru City is not a city with numerous of earthquakes, but Pekanbaru City had ever felt the impact of the earthquake on September, 2009. The earthquake took place on West Sumatera, was caused by frictions between two plates, which were Eurasia Plate and Indo-Australia Plate. To anticipate a bad impact that would happened by earthquake, therefore it is necessary to evaluate the building`s vulnerability against earthquake by using FEMAP 154. The vulnerability of the each buildings toward earthquake are different. This is based on the non structural components on the buildings which would influenced the evaluation result later. From the research, it shown that the vulnerability of the buildings in some places in Pekanbaru City are quite well. It proved by the building`s vulnerability analysis against earthquake had fulfilled the evaluation of FEMAP 154 Keywords : Earthquake, Vulnerability, FEMAP-154.